Philosophy of art: A contemporary introduction - Carroll, Noël (London Routledge, 1999)
Philosophy of Art is a textbook for undergraduate students interested in the topic of philosophical aesthetics.It introduces the techniques of analytic philosophy as well as key topics such as the representational theory of art, formalism, neo-formalism, aesthetic theories of art, neo-Wittgensteinism, the Institutional Theory of Art. as well as historical approaches to the nature of art.Throughout, abstract philosophical theories are illustrated by examples of both traditional and contemporary art including frequent reference to the avant-garde in this way enriching the readers understanding of art theory as well as the appreciation of art.Unique features of the textbook are:* chapter summaries* summaries of major theories of art and suggested analyses of the important categories used when talking and thinking of art* annotated suggested readings at the ends of chapters.